Study on Accurate Temperature Measurement Using Different Sensors and Microcontroller Based System - Nath, Jayanta Kumar; Baruah, Himadri (International Journal of Computer Sciences and Engineering, 2025)
Much of technology advances in the field of temperature measurement have led to a huge variety of sensors and measuring instruments now being available for making accurate measurements at relatively low costs. This paper makes an attempt to do a study on improving the accuracy of temperature measurement using most popular temperature measurement sensors and implementing in a microcontroller based measurement system, that will help to choose the correct method and sensor for specific application of temperature measurement.